ANALISIS PERENCANAAN REAKTOR BIOGAS KAP 16 m3 DENGAN PEMANFAATAN KOTORAN MANUSIA - Imam Kholiq; Muharom Muharom (Journal of Engineering and Management in Industrial System, 2015)
Abstract The effort of searching about cheaper fuel alternative and environment friendly was solution for problem in rare fuel. This paper examine potential energy from renewable source. Design in reactor with 16m3 capacity for retain feces from 200 human. Based on calculation from the design, this reactor can produce biogas about 4m3/day. Air methane affected by ratio input of C/N (human fecess), time of residence, pH, temperature, and toxicity. Digester temperature about 25–27oC and pH 7–7,8 produced biogas with composition of methane air about 77%. For using this gas we need level of pressure 4 mm H2O and biogas level at 0.23 m3/hour. Beside this if we want for household activities for example cooking we need biogas 0.30 m3/hour with level pressure at  75 mmH2O. The analysis for effect on environment from mud that produced from reactor shown decreasing at COD about 90% from  new material condition. The comparing of  BOD/COD about  0,37 smaller than normal condition from liquid waste that have BOD/COD=0,5. And the other benefit we get analysis of composition N, P dan K shown same result that we get at fertilizer.